A Simple Logging System for Safe Internet Use - Demirol, Doygun; Tuna, Gurkan; Das, Resul (Ieee, 2017)
Although the Internet offers numerous advantages, it raises many information security risks, especially against young people and children, who are today amongst the largest user groups of mobile and online technologies all around the world. Therefore, to empower and protect Internet users, it is necessary to develop proper strategies and tools to encapsulate their needs, and identify and prevent all types of the information security risks that may arise during the use of the Internet. In this study, a tracking system to ensure the safe use of the Internet is proposed. Considering the distribution of its potential users, the system has an easy-to-use graphical user interface. By recognizing dangerous web sites and IP addresses, the proposed system blocks access to those sites and this way provides reliable Internet access to its users. During the Internet access, it analyzes accessed IP addresses and port numbers in terms of access type and time and informs the user of the corresponding port numbers which must be closed for safe Internet access. Moreover, by continuously checking the host redirection file of the computer it runs on, it identifies redirections from web addresses to specific IP addresses and this way provides protection against phishing attacks which are becoming one of the most common Internet threats. Although the proposed system is a simple application since it is an open source, freeware application designed for children, it can be improved to consider more sophisticated attack types.
2017 International Artificial Intelligence and Data Processing Symposium (IDAP) -- SEP 16-17, 2017 -- Malatya, TURKEY
Keywords: Internet; Internet Use; Information Security; Logging